Differences in perceived travel distance from central versus peripheral optic flow are the same when standing and walking - Ambika Bansal; Hongyi Guo; Robert S. Allison; Laurence R. Harris (PLoS ONE, 2026)
The continuously evolving ways in which people move challenges our ability to process self-motion. Previous research from our lab has shown that when seated, optic flow presented in the far periphery results in people feeling they moved further than when the same motion was presented over the full field or in the central field only. The literature is mixed on the relative weightings of visual and non-visual cues when estimating travel distance, and it is unknown how non-visual cues might affect the use of optic flow in the far periphery. Here, we used a large-field edgeless display to visually “move” participants. Participants were either (i) physically stationary (visual-only condition), (ii) performing a blindfolded walking task on a treadmill (blindfolded walking condition), or (iii) visually “moving” while walking on a treadmill (visual-and-treadmill condition). Optic flow simulating forward self-motion was presented either full field, in the central field (inside 40°), or in the far periphery (outside 180°). Participants estimated travel distances by stopping at the location of a previously seen target (Move-To-Target Task) or adjusting a target to indicate the distance of a previous movement (Adjust-Target Task). In the Move-To-Target task, peripheral optic flow led to higher gains (perceived travel distance/ actual travel distance) compared to the central field and full-field conditions during both the visual-only and visual-and-treadmill conditions. In the same task, the blindfolded walking condition also led to higher gains than the visual-only or visual-and-treadmill conditions. In the Adjust-Target task, there were no significant differences between conditions. There were also no interaction effects in either task between field-of-view, and whether participants were standing or walking. This implies that the high sensitivity to optic flow in the far periphery is a general feature of perceptual odometry even when integrating non-visual cues with visual cues.